2018
DOI: 10.1073/pnas.1806908115
|View full text |Cite
|
Sign up to set email alerts
|

Functional muscle recovery with nanoparticle-directed M2 macrophage polarization in mice

Abstract: Persistence of inflammation, and associated limits in tissue regeneration, are believed to be due in part to the imbalance of M1 over M2 macrophages. Here, we hypothesized that providing a sustained source of an antiinflammatory polarizing cytokine would shift the balance of macrophages at a site of tissue damage to improve functional regeneration. Specifically, IL-4-conjugated gold nanoparticles (PA4) were injected into injured murine skeletal muscle, resulting in improved histology and an ∼40% increase in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 51 publications
3
118
0
Order By: Relevance
“…Interestingly, these fibres are not blocked in their growth, but they rather undergo a temporary delay, showing, after a longer time period, several fully matured fibres with peripheral nuclei. In line with our results, a recent study showed that IL4‐conjugated gold nanoparticles injected into injured murine skeletal muscle improved muscle histology and performance associated with two‐fold increase of type II macrophages …”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, these fibres are not blocked in their growth, but they rather undergo a temporary delay, showing, after a longer time period, several fully matured fibres with peripheral nuclei. In line with our results, a recent study showed that IL4‐conjugated gold nanoparticles injected into injured murine skeletal muscle improved muscle histology and performance associated with two‐fold increase of type II macrophages …”
Section: Discussionsupporting
confidence: 92%
“…While the backpacks described here bind to macrophage surfaces, other designs can be conceived to attach to other circulatory cells with higher chemotactic sensitivity (17,18,55). Also, a range of immunomodulatory payloads can be considered, including those that facilitate adaptive immune responses toward a backpack-based vaccine (52) or promote anti-inflammatory phenotypes to aid in tissue regeneration or repair for autoimmune diseases (56,57). PDMS template preparation PDMS templates were prepared by soft lithography using methods similar to those described previously (16).…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, the same group conjugated chemotherapeutic agents to the spiky gold nanoparticles to achieve chemo‐photothermal combination therapy, which generated free antigens and induced potent antitumor immunity against disseminated tumors . In the same year, Mooney and co‐workers synthesized IL‐4‐conjugated gold nanoparticles to manipulate macrophage phenotypes for muscle function recovery . The authors showed that infiltrating macrophages can be repolarized from M1 to M2 phenotypes in a superior manner compared to empty vesicles and soluble IL‐4, establishing the utility of gold nanoparticles for inflammatory injuries and diseases.…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%